SISTEM PENDUKUNG KEPUTUSAN PEMBERIAN BEASISWA DI POLITEKNIK NEGERI SRIWIJAYA MENGGUNAKAN METODE FUZZY LOGIC TSUKAMOTO - Suryati Suryati; M. Ricky Hikmawan; Rendra Gustriansyah (Jurnal Informatika Global)
Sriwijaya State Polytechnic Joint Government and Private Parties have had the scholarship program to students who beprestasi and can not afford. Therefore scholarship should be awarded to eligible recipients and deserve to get it. However, in the selection of the scholarship will certainly experience difficulties because of the large number of scholarship applicants and the criteria used to determine the grantee's decision as expected and acceptance of the scholarship has a maximum limit of quotas. It required a study that aims to take into account all criteria decision support to help accelerate and simplify the decision making process. In the selection of the scholarship recipients to take a little longer and less efficient. Besides it takes a long time in the electoral process and the establishment of scholarships also there are opportunities to make the wrong decisions because the process is subjectivity. Therefore made a decision support system that can perform calculations on all the criteria for the selection of scholarship recipients at State Polytechnic of Sriwijaya. The method used in the decision making is the scholarship selection Tsukamoto fuzzy logic method, this method selected because it is able to select the best alternative from a number of alternatives, in this case the alternative meant that students are eligible to receive scholarships based on certain criteria.Keywords: DSS, Fuzzy Logic, Tsukamoto, Scholarships